Programas estadisticos, aplicado al proceso enseñamza- aprendisaje en los estudiantes del primero de bachillerato de la Unidad Educativa 24 de Mayi, del Canton Quevedo año 2017 - Figueroa Nivela, Veronica Johanna (2019)
It is a statistics package that performs and applies basic and advanced statistical functions. The software was created in 1980 by Dr. Neil Polhemus while he was working as a professor of statistics at the University of Pricenton. The CURRENT version of STATGRAPHICS CENTURION XVII PROGRAM was released in the fall of 2014 and version xvii, available in 32-bit and 64-bit edition, is available in five languages: English, French, Spanish, German and Italian. It is a compliance for Microsoft Excel that allows users to perform various calculations necessary when learning or explaining six sigma adds a menu selection to Excel that contains section for each element of the dmaic paradigm (define measure analyze improve and control, in addition to menu items Additional Tools and Help The program is designed to meet the needs of Six Sigma Yellow Belts, Green Belts, and most Sigma Express Black Belts. It is available in English and French. It is a statistical program that is very easy to access and easy to use. In October 2014, Stapoint Technologies Incorporated launched Centurion xvii, the company's flagship software, Centurion xvii included 32 new statistical procedures. With Centurion xvii, the company placed a new emphasis on data visualization. After extensive development Stagraphics launched its cloud-based status in June 2015, billing as one of the first cloud analytics tools on the market, it is designed by Incorporated Technologies to work on PCs, Macs, tablets and handheld devices.